Pengaruh Profitabilitas, Ukuran Perusahaan, Ukuran Kantor Akuntan Publik Dan Kompleksitas Operasi Perusahaan Terhadap Audit Delay (Studi Empiris Pada Perusahaan Sub Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia tahun 2019-2021) - Gracia Maria Verdiani Putri; Siti Asiah Murni (LPPM Universitas Wijaya Kusuma Surabaya, 2024)
The goal of this study is to be able to demonstrate empirically how profitability, company size, the size of public accounting firms, and the complexity of business processes affect audit delays. The secondary data used in this research, which is quantitative in nature, was gleaned from the company's annual report. Manufacturing firms in the mining industry that will be listed on the Indonesia Stock Exchange in 2019 through 2021 make up the study's population. The purposive sampling strategy was used in this investigation. 18 companies with observation methods for three years in a row made up the sample that satisfied the requirements of this study, making a total of 54 data the sample for this research. Multiple linear regression analysis utilizing the spss software version 25 is the data analysis method used. According to the study's findings, profitability has a negative impact on audit delay. The audit delay is positively impacted by the company's size. The length of the audit is negatively impacted by the public accounting firm's size. The delay in the audit is positively impacted by the company's activities being complex